Aggregated and Hyperstable Damage-Associated Molecular Patterns Are Released During ER Stress to Modulate Immune Function - Andersohn, Alexander; Garcia, M. Iveth; Fan, Ying; Thompson, Max C.; Akimzhanov, Askar M.; Abdullahi, Abdikarim; Jeschke, Marc G.; Boehning, Darren (Frontiers in Cell and Developmental Biology, 2019)
Chronic ER stress occurs when protein misfolding in the ER lumen remains unresolved despite activation of the unfolded protein response. We have shown that traumatic injury such as a severe burn leads to chronic ER stress in vivo leading to systemic inflammation which can last for more than a year. The mechanisms linking chronic ER stress to systemic inflammatory responses are not clear. Here we show that induction of chronic ER stress leads to the release of known and novel damage-associated molecular patterns (DAMPs). The secreted DAMPs are aggregated and markedly protease resistant. ER stress-derived DAMPs activate dendritic cells which are then capable of polarizing naïve T cells. Our findings indicate that induction of chronic ER stress may lead to the release of hyperstable DAMPs into the circulation resulting in persistent systemic inflammation and adverse outcomes.